EDUKASI MASYARAKAT TENTANG POLA HIDUP SEHAT MELALUI PROGRAM PENYULUHAN DI KELURAHAN SUKAMULYA - Pusnita, Indah; Sakir, Icuk Muhammad; Triana, Eny; Ariansyah, Sarvika; Nuryantini, Nira (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2021)
Health is a fundamental aspect of human life that affects the quality of life both individually and collectively. One strategy to improve public health is by implementing Clean and Healthy Living Behavior (PHBS), which includes habits such as maintaining personal and environmental hygiene, consuming nutritious food, engaging in physical activity, and preventing diseases. However, low public awareness in adopting PHBS remains a challenge, especially in areas with limited access to health information. This study aims to enhance public understanding of a healthy lifestyle through a participatory-based counseling program in Sukamulya Village. The methods used include interactive lectures, practical demonstrations, and group discussions to encourage active community involvement. The counseling results indicate an increased understanding of the importance of a balanced diet, physical activity, and environmental cleanliness. Although challenges such as limited access to nutritious food and sports facilities persist, continuous education and collaboration among various stakeholders are expected to strengthen the optimal implementation of PHBS. Thus, a community-based counseling approach can serve as an effective solution to raise awareness and drive behavioral changes toward a healthier lifestyle.